Pathogenesis of Keratinocyte Carcinomas and the Therapeutic Potential of Medicinal Plants and Phytochemicals - Andrea Jess Josiah; Danielle Twilley; Sreejarani Kesavan Pillai; Suprakas Sinha Ray; Namrita Lall (Molecules, 2021)
Keratinocyte carcinoma (KC) is a form of skin cancer that develops in keratinocytes, which are the predominant cells present in the epidermis layer of the skin. Keratinocyte carcinoma comprises two sub-types, namely basal cell carcinoma (BCC) and squamous cell carcinoma (SCC). This review provides a holistic literature assessment of the origin, diagnosis methods, contributing factors, and current topical treatments of KC. Additionally, it explores the increase in KC cases that occurred globally over the past ten years. One of the principal concepts highlighted in this article is the adverse effects linked to conventional treatment methods of KC and how novel treatment strategies that combine phytochemistry and transdermal drug delivery systems offer an alternative approach for treatment. However, more in vitro and in vivo studies are required to fully assess the efficacy, mechanism of action, and safety profile of these phytochemical based transdermal chemotherapeutics.